Application Of Criminal Sanctions Against Corporations As Subjects Law On Burning Forest Which Cause Damage Environment - Ismaidar Ismaidar; Tengku Riza Zarzani; Suramin Suramin (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Forest fires are an environmental problem that occurs so often that it has become a local and global concerns. The phenomenon of forest and land fires that occurred in various regions of Indonesia several years ago is a legal fact that the implementation of Law Number 32 of 2009 concerning Environmental Protection and Management, Law Numbers 19 of 2004 concerning Forestry and various other statutory regulations does note in understand with predetermined expectations and rules. It cannot be denied that the phenomenon.phenomenon of forests fires is a serious and urgent threat that must be addressed by all parties. The method used in this research is normative legal research whichcomes from primary data, secondary data and tertiary data to support the arguments in this article. The data collection technique is qualitative descriptive analysis, namely by taking a conceptual and statutory approach. Using literature studies by collecting data through books, articles, statutory regulations, journals or other legal literature as well as online sites that are relevant to the problem being written about. This research aims to determine the impact of forest fires which cause environmental damage, the application of criminal sanctions against corporations as legal subjects for criminal acts of forest burning which . Based on the description above, it can be concluded that in accordance with the development of Indonesian criminal law regulations, a corporation that is declared obstacles faced when applying criminal sanctions against corporations as legal subjects for criminal acts of forest burning which cause environmental damage legal subject can also be burdened with criminal liability. Corporations that have been proven to have burned forests